Knowledge, attitudes and behaviors associated with mental illness among the working population in Hong Kong: a cross-sectional telephone survey. Issue 3 (2nd July 2016) - Zhu, Shimin; Tse, Samson; Tang, Jessica; Wong, Paul
ABSTRACT: Mental health-related issues such as stress and depressive symptoms are common in the workplace and costly to both employees and employers. Stigma against mental illness limits one's help-seeking attitudes and behavior, thereby leading to social isolation and deteriorating performance in the workplace. This study aimed at examining what aspects of knowledge, attitude and previous contacts with people with mental illness influence working adults' intention to have future contact with people (e.g., to work with, to live nearby) with mental illness. A total of 1031 employees across eight industries were telephone-interviewed. Descriptive analysis and hierarchical logistic regression were performed. The patterns of knowledge, attitude and behaviors were similar across industries. Higher education and lower income level were associated with higher intention to have contact with people with mental illness. Previous contacts were significant predictors of intention of future contacts. The attitude that people with mental health problems are less reliable was significantly associated with lower intention, and the knowledge that people with severe mental health problems can fully recover was significantly associated with higher intended contacts with people with mental illness. The implication of the findings and the cultural and contextual influences are discussed.